2009
DOI: 10.1038/mp.2009.77
|View full text |Cite
|
Sign up to set email alerts
|

Passive transfer of streptococcus-induced antibodies reproduces behavioral disturbances in a mouse model of pediatric autoimmune neuropsychiatric disorders associated with streptococcal infection

Abstract: Streptococcal infections can induce obsessive-compulsive and tic disorders. In children, this syndrome, frequently associated with disturbances in attention, learning and mood, has been designated pediatric autoimmune neuropsychiatric disorders associated with streptococcal infection (PANDAS). Autoantibodies recognizing central nervous system (CNS) epitopes are found in sera of most PANDAS subjects, but may not be unique to this neuropsychiatric subset. In support of a humoral immune mechanism, clinical improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
125
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(142 citation statements)
references
References 63 publications
12
125
2
1
Order By: Relevance
“…A subset of these mice developed motoric and behavioral disturbances that were correlated with immunoreactivity to the deep cerebellar nuclei (Hoffman et al, 2004). In a subsequent study, passive transfer of antistreptococcal sera from immunized mice to naive mice (concomitant with lipopolysaccharides (LPS) to break the blood brain barrier) resulted in antibody deposition in the hippocampus and in the development of motoric and behavioral disturbances similar to those seen in immunized mice (Yaddanapudi et al, 2009). Both studies (Hoffman et al, 2004;Yaddanapudi et al, 2009) support a role for antibodies in the induction of behavioral alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of these mice developed motoric and behavioral disturbances that were correlated with immunoreactivity to the deep cerebellar nuclei (Hoffman et al, 2004). In a subsequent study, passive transfer of antistreptococcal sera from immunized mice to naive mice (concomitant with lipopolysaccharides (LPS) to break the blood brain barrier) resulted in antibody deposition in the hippocampus and in the development of motoric and behavioral disturbances similar to those seen in immunized mice (Yaddanapudi et al, 2009). Both studies (Hoffman et al, 2004;Yaddanapudi et al, 2009) support a role for antibodies in the induction of behavioral alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study, passive transfer of antistreptococcal sera from immunized mice to naive mice (concomitant with lipopolysaccharides (LPS) to break the blood brain barrier) resulted in antibody deposition in the hippocampus and in the development of motoric and behavioral disturbances similar to those seen in immunized mice (Yaddanapudi et al, 2009). Both studies (Hoffman et al, 2004;Yaddanapudi et al, 2009) support a role for antibodies in the induction of behavioral alterations. Although the mouse model was successful in showing behavioral changes in streptococcal-immunized mice and was related to passively transferred antibody, it did not investigate specific neural and immune characteristics reported previously in SC and PANDAS (Husby et al, 1976;Kirvan et al, 2003Kirvan et al, , 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the same group extended this model by examining whether peripheral anti-CNS antibodies are sufficient to reproduce the syndrome, and whether or not the effect is eliminated by depleting IgG before transfer into naive mice (Yaddanapudi et al 2009). Their results demonstrated that the immunized animals showed stereotypic behaviors as well as deficits in motor coordination, learning/memory, and social interaction.…”
Section: Animal Modelsmentioning
confidence: 99%
“…As GAS infections in youth are common and possibly coincidental in this population, it is also difficult to establish causality in those patients who test positive. However, there has been a substantial body of literature linking GAS infections with OCD, eating restriction, and movement disorders including chorea and tics (Husby et al 1976;Swedo et al 1989Swedo et al , 1993Swedo et al , 1998Mercadante et al 2000;Leonard and Swedo 2001;Kirvan et al 2003;Hoffman et al 2004;Singer et al 2004;Kirvan et al 2006Kirvan et al , 2007Murphy et al 2007;Yaddanapudi et al 2010;Brimberg et al 2012;Lotan et al 2014;Toufexis et al 2014;Williams and Swedo 2014). …”
mentioning
confidence: 99%